(untitled) (Proceedings of the International Conference on Public Health, 2022)
Background: The COVID-19 pandemic has seriously impacted children’s efforts to develop Autism Syndrome Disorder (ASD). The role of family and the closest community is significant in providing support and assistance for ASD individuals while at home. The study aims to develop a family and community empowerment model for handling autistic children by integrating multisectoral stakeholder policies and programs. Methods: The qualitative study in Surabaya with purposive sampling. Data collection by indepth interview with ASD parents and FGD with 16 multisector stakeholders. Results: Family and community constraints in handling autistic children in Surabaya were the low parental responsiveness to monitoring child development, early detection, therapy assistance, lack of communication, information and access to professional ASD health service and education facilities, and limited access to services for autistic children, neglected, and social problems. In addition, the study identified challenges in implementing policies and program strategies for dealing with ASD stakeholders: health service facilities and ASD education are still lacking, lack of infrastructure, curriculum, implementation of human resources and financing, and the dissemination of regulations has not been intensive and sustainable. Conclusion: The study developed a family empowerment model in handling autistic children involving multisectoral stakeholders by synergizing policies and programs, especially in health, education, social, religion, women’s empowerment, and child protection supported by governments. We can implement the model by advocating stakeholders to pursue with a shared commitment and formulating program activities, also financing needed to implement activities.